Betanin‐Enriched Red Beetroot (Beta vulgaris L.) Extract Induces Apoptosis and Autophagic Cell Death in MCF‐7 Cells. (14th October 2015) - Nowacki, Laëtitia; Vigneron, Pascale; Rotellini, Laura; Cazzola, Hélène; Merlier, Franck; Prost, Elise; Ralanairina, Robert; Gadonna, Jean‐Pierre; Rossi, Claire; Vayssade, Muriel
Abstract : Recent studies have pointed out the preventive role of beetroot extracts against cancers and their cytotoxic activity on cancer cells. Among many different natural compounds, these extracts contained betanin and its stereoisomer isobetanin, which belongs to the betalain group of highly bioavailable antioxidants. However, a precise identification of the molecules responsible for this tumor‐inhibitory effect was still required. We isolated a betanin/isobetanin concentrate from fresh beetroots, corresponding to the highest purified betanin extract used for studying anticancer activities of these molecules. The cytotoxicity of this betanin‐enriched extract was then characterized on cancer and normal cells and we highlighted the death signalling pathways involved. Betanin/isobetanin concentrate significantly decreased cancer cell proliferation and viability. Particularly in MCF‐7‐treated cells, the expressions of apoptosis‐related proteins (Bad, TRAILR4, FAS, p53) were strongly increased and the mitochondrial membrane potential was altered, demonstrating the involvement of both intrinsic and extrinsic apoptotic pathways. Autophagosome vesicles in MCF‐7‐treated cells were observed, also suggesting autophagic cell death upon betanin/isobetanin treatment. Importantly, the betanin‐enriched extract had no obvious effect towards normal cell lines. Our data bring new insight to consider the betanin/isobetanin mix as therapeutic anticancer compound, alone or in combination with classical chemotherapeutic drugs, especially in functional p53 tumors. Copyright © 2015 John Wiley & Sons, Ltd.